The Film in Hand Modes of Coordination and Assisted Virtuosity in the Bombay Film Studios - Grimaud, Emmanuel (Qualitative Sociology Review, 2007)
Less has been said about the hand movements of the film makers, their cultural dimension and the place of this "corporate language" in the film making process, probably because this object is difficult to capture even with a diary. Gestures go too fast to be sketched on the spot and often faster than the perception of the ethnographer. Some of these gestures are made to stabilize the frame or simulate the camera movement but lots of them are difficult to classify and don’t fall into this category, like the ones which are produced to accompany the actors’ action or to invite him to perform a certain action and which have more to do with a mode of demonstration involving the entire body. This article, mostly based on videos of Bombay film makers at work, tries to identify the specificity of these gestures in terms of communication or interaction and their potential of coordination in the film set dynamics.